Cartography of Sound: Body-Mapping and Border-Crossings in Kay Ulanday Barrett’s More Than Organs and Aldrin Valdez’s ESL, or You Weren’t Here - Alvarado, Jo (The Columbia Journal of Asia, 2022)
This paper embarks on the odyssey of queer diasporic Pilipinxs, a journey that has hitherto been neglected in English literary studies. Set against the backdrop of multiple imperialisms and ongoing migration, this project attends to a complex array of issues discussed in contemporary queer Pilipinx American poetry, examining bodies in transit, bodies in translation, and bodies in transformation. In close-reading Kay Ulanday Barrett’s More Than Organs and Aldrin Valdez’s ESL, or You Weren’t Here, my aim is to explore how queer Pilipinx American embodiment can be uprooted and mapped within a poetic landscape that dissolves boundaries between languages, voices, genders, temporalities, and worlds. These collections elucidate not only alternative ways of mourning and healing but also the breadth of queer, diasporic imagination that transcends neat categorization or stringent conclusions. This thesis proposes that queer Pilipinx American poetry can help us negotiate our vexed legacies in order to arrive at new, expansive possibilities of being, becoming, and belonging.